Answer:
(-3,-2)
Step-by-step explanation:
Starting at the point (1, 0)
Now we move don 2 units (so the y-value reduces in two units) making now the point (1,0-2) which is (1, -2)
then we move to the left 4 units (so the x-value has now to be decreased in 4 units) making the point: (1-4, -2) which is (-3, -2)
Answer:
x=1
Step-by-step explanation:
Divide both sides by the numeric factor on the left side then solve.
Hope this helps.
Answer:
y = -2x^2(x - 3)
Step-by-step explanation:
<em><u>Preliminary Remark</u></em>
If a cubic is tangent to the x axis at 0,0
Then the equation must be related to y = a*x^2(x - h)
<em><u>(3,0)</u></em>
If the cubic goes through the point (3,0), then the equation will become
0 = a*3^2(3 - h)
0 = 9a (3 - h)
0 = 27a - 9ah
from which h = 3
<em><u>From the second point, we get</u></em>
4 = ax^2(x - 3)
4 = a(1)^2(1 - 3)
4 = a(-2)
a = 4 / - 2
a = -2
<em><u>Answer</u></em>
y = -2x^2(x - 3)
2:12 is an equivalent ratio